2005
DOI: 10.1002/cjg2.755
|View full text |Cite
|
Sign up to set email alerts
|

The Effect and Correction of Non-Tectonic Crustal Deformation on Continuous GPS Position Time Series

Abstract: GPS observed crustal deformation usually includes both tectonic and non‐tectonic deformation signals, and it is vitally important to remove the non‐tectonic deformation signals in the data in order to effectively use GPS observations for tectonic deformation studies. Using the Earth satellite data and geophysical models, we calculate non‐tectonic crustal deformation caused by the ocean tide loading, atmospheric mass loading, snow and soil moisture mass loading, and non‐tidal ocean mass loading. Based on the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 14 publications
1
30
0
1
Order By: Relevance
“…the Up component of DLFT (Delft, the Netherlands station) is greater than one centimeter, which is consistent with the study results From the above analysis, we can see that even though the loading effect is close to zero average for long time series, the instantaneous impact on GPS time series is non-trivial, especially for high-precision geophysical studies. Besides, the results indicate that the loading effect behaves with regional difference in spatial scale, and this explains why there is significant disagreement on the effect of environmental loading on GPS position time series from various authors (Dong et al, 2002;Wang et al, 2005;Yuan et al, 2008;Yan et al, 2009;Rietboek et al, 2011;Jiang et al, 2013).…”
Section: Statistical Analysis Of Loading Time Seriesmentioning
confidence: 90%
See 1 more Smart Citation
“…the Up component of DLFT (Delft, the Netherlands station) is greater than one centimeter, which is consistent with the study results From the above analysis, we can see that even though the loading effect is close to zero average for long time series, the instantaneous impact on GPS time series is non-trivial, especially for high-precision geophysical studies. Besides, the results indicate that the loading effect behaves with regional difference in spatial scale, and this explains why there is significant disagreement on the effect of environmental loading on GPS position time series from various authors (Dong et al, 2002;Wang et al, 2005;Yuan et al, 2008;Yan et al, 2009;Rietboek et al, 2011;Jiang et al, 2013).…”
Section: Statistical Analysis Of Loading Time Seriesmentioning
confidence: 90%
“…Dong et al (2002) assumed that less than half of the observed GPS seasonal variation could be explained by redistributions of environmental surface mass loads. Wang et al (2005) quantified the effects of ocean tides, atmospheric pressure, snow depth and soil moisture, non-tide ocean loading (NTOL) on the position time series of GPS stations. They demonstrated that these environmental loads could reduce the RMS of the station vertical position by about 1 mm or about 11 % of the total RMS (root mean square).…”
Section: Environmental Loading Dataset and Processingmentioning
confidence: 99%
“…The GPS time series in the horizontal direction are featured with the linear velocity caused by plate movement, and in the vertical direction with more cyclical variation caused by geophysical phenomena such as non-tectonic deformation. Some researches show that the mass loading can explain most seasonal variations estimated in vertical GPS time series Wang et al 2005;Zhang et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…With accumulated continuous GPS (CGPS) observation data, it is now possible to comprehensively analyze the effect of the time series span on the establishment of the inferred noise model and thus on the likely velocities and their uncertainties (Langbein and Johnson, 1997;Zhu et al, 2003;Wang et al, 2005Wang et al, , 2008Cheng et al, 2008;Yang et al, 2008;Tian and Shen, 2009;Jiang and Liu, 2010;Yuan et al, 2010;Chen et al, 2012;Wang et al, 2013).…”
mentioning
confidence: 97%